Alkaloid inspired spirocyclic oxindoles from 1,3-dipolar cycloaddition of pyridinium ylides - Day, Jonathan; Uroos, Maliha; Castledine, Richard A.; Lewis, William; McKeever-Abbas, Ben; Dowden, James (Royal Society of Chemistry, 2013)
Cycloaddition reactions between pyridinium ylides and 3-alkenyl oxindoles that proceed in high yield and with very good regio- and diastereoselectivity are reported. The resulting cycloadducts have the same stereochemistry of biologically active oxindole alkaloids, such as strychnofoline.